Integrated Science Learning with Peatland Ecosystem Knowledge - Maolina Asi; Amin Retnoningsih; Andin Irsadi (Universitas Negeri Semarang, 2021)
Science learning associated with Socio Scientific Issues has the potential to increase scientific and environmental literacy. This research is a qualitative study with a survey method to analyze the impact of socio-scientific issues on the peat environment through the frequency of its implementation in science learning, students' initial knowledge and opinions about peat, and the types of media for peat recognition. This research is a preliminary study to develop science learning media that can improve scientific and environmental literacy about peat in Central Kalimantan.[U1] Subyek of this research were 83 junior high school students at SMPN 5 Palangka Raya and SMPN 7 Cempaga, Central Kalimantan. The results showed that as many as 29.8% of students had never studied peat. Their knowledge was limited to a general knowledge of peat from the internet. The needs analysis results show that almost all students (99%) need peat introduction media, 65% choose video media, 23% choose educational games, and the rest choose electronic books. The type of media needed by these students is a reference for developing interactive learning media to introduce peatland.